28.8k views
3 votes
Solenoid A has total number of turns N length L and diameter D. Solenoid B has total number of turns 2N, length 2L and diameter 2D. Inductance of solenoid A is

8 times inductance of solenoid B
1/4 of inductance of solenoid B
same as inductance of solenoid B
1/8 of inductance of solenoid B
four times of inductance of solenoid B

User Gabra
by
4.9k points

2 Answers

6 votes

Hi there!

We can begin by calculating the inductance of a solenoid.

Recall:

L = (\Phi _B)/(i)

L = Inductance (H)
φ = Magnetic Flux (Wb)

i = Current (A)

We can solve for the inductance of a solenoid. We know that its magnetic field is equivalent to:

B = \mu _0 (N)/(L)i

And that the magnetic flux is equivalent to:

\Phi _B = \int B \cdot dA = B \cdot A

Thus, the magnetic flux is equivalent to:

\Phi _B = \mu _0 (N)/(L)iA

The area for the solenoid is the # of loops multiplied by the cross-section area, so:

A_(total)= N * A


\Phi _B = \mu _0 (N^2)/(L)iA

Using this equation, we can find how it would change if the given parameters are altered:

\Phi_B ' = \mu_0 ((2N)^2)/(2L) i * 4A

**The area will quadruple since a circle's area is 2-D, and you are doubling its diameter.


\Phi'_B = (4)/(2) * 4(\mu_0 (N)/(L)iA) = 8\mu_0 (N)/(L)iA

Thus, Solenoid B is 8 times as large as Solenoid A.

Solenoid A is 1/8 of the inductance of solenoid B.

User Nakul Narayanan
by
5.4k points
2 votes

Answer:

∴Inductance of solenoid A is
\frac18 of inductance of solenoid B.

Step-by-step explanation:

Inductance of a solenoid is


L=N\frac\phi I


=N(B.A)/(I)


=N(\mu_0NI)/(l.I)A


=(\mu_0N^2A)/(l)


=(\mu_0N^2)/(l).\pi(\frac d2)^2


=\mu_0\pi(N^2d^2)/(4l)

N= number of turns


l = length of the solenoid

d= diameter of the solenoid

A=cross section area

B=magnetic induction


\phi = magnetic flux


I= Current

Given that, Solenoid A has total number of turns N, length L and diameter D

The inductance of solenoid A is


=\mu_0\pi(N^2D^2)/(4L)

Solenoid B has total number of turns 2N, length 2L and diameter 2D

The inductance of solenoid B is


=\mu_0\pi((2N)^2(2D)^2)/(4.2L)


=\mu_0\pi(16 N^2D^2)/(4.2L)

Therefore,


\frac {\textrm{Inductance of A}}{\textrm{Inductance of B}}=(\mu_0\pi(N^2D^2)/(4L))/(\mu_0\pi(16 N^2D^2)/(4.2L))


\Rightarrow \frac {\textrm{Inductance of A}}{\textrm{Inductance of B}}=\frac18


\Rightarrow {\textrm{Inductance of A}}=\frac18* {\textrm{Inductance of B}}

∴Inductance of solenoid A is
\frac18 of inductance of solenoid B.

User Feras Taleb
by
4.9k points